THE USE OF LAVENDER ESSENTIAL OIL IN AROMATHERAPY - Zokirjonov Asilbek Dilshodjonovich; Jalilov Fazliddin Sodikovich (Innovate Conferences, 2025)
Lavender essential oil, derived primarily from Lavandula angustifolia, has been widely used in aromatherapy due to its calming, anxiolytic, and analgesic properties. This paper explores the botanical background, chemical profile, and therapeutic applications of lavender essential oil. A review of current literature highlights its effectiveness in reducing stress, improving sleep, and managing mild anxiety and pain. While scientific support continues to grow, further standardized clinical studies are necessary to fully integrate lavender essential oil into evidence-based healthcare practices.
Keywords: Lavender essential oil, Lavandula angustifolia, aromatherapy, linalool, anxiety, sleep, stress relief, complementary medicine